Ginkgotides: Proline-Rich Hevein-Like Peptides from Gymnosperm Ginkgo biloba - Wong, Ka H.; Tan, Wei Liang; Serra, Aida; Xiao, Tianshu; Sze, Siu Kwan; Yang, Daiwen; Tam, James P. (Frontiers in Plant Science, 2016)
Hevein and hevein-like peptides belong to the family of chitin-binding cysteine-rich peptides. They are classified into three subfamilies, the prototypic 8C- and the 6C- and 10C-hevein-like peptides. Thus far, only five 8C-hevein-like peptides have been characterized from three angiosperms and none from gymnosperm. To determine their occurrence and distribution in the gymnosperm, Ginkgo biloba leaves were examined. Here, we report the discovery and characterization of eleven novel 8C-hevein-like peptides, namely ginkgotides gB1–gB11. Proteomic analysis showed that the ginkgotides contain 41–44 amino acids (aa), a chitin-binding domain and are Pro-rich, a distinguishing feature that differs from other hevein-like peptides. Solution 1H-NMR structure determination revealed that gB5 contains a three β-stranded structure shaped by a cystine knot with an additional disulfide bond at the C-terminus. Transcriptomic analysis showed that the ginkgotide precursors contain a three-domain architecture, comprised of a C-terminal tail (20 aa) that is significantly shorter than those of other 8C- and 10C-hevein-like peptides, which generally contain a protein cargo such as a Barwin-like protein (126 aa) or class I chitinase (254 aa). Transcriptomic data mining found an additional 48 ginkgotide homologs in 39 different gymnosperms. Phylogenetic analysis revealed that ginkgotides and their homologs belong to a new class of 8C-hevein-like peptides. Stability studies showed that ginkgotides are highly resistant to thermal, acidic and endopeptidase degradation. Ginkgotides flanked at both the N- and C-terminal ends by Pro were resistant to exopeptidase degradation by carboxypeptidase A and aminopeptidase. Antifungal assays showed that ginkgotides inhibit the hyphal growth of phyto-pathogenic fungi. Taken together, ginkgotides represent the first suite of hevein-like peptides isolated and characterized from gymnosperms. As a group, they represent a novel class of 8C-hevein-like peptides that are Pro-rich and protein-cargo free. Our findings also suggest that the ginkgotide scaffold could be useful for engineering metabolic-stable peptide therapeutics.